Van stof tot asse : 5 jaar Galerij De Ziener. - De Smedt, Jan (Asse : [s.n.], 1990)
Bervoets, Fred ; Daled, Jeroen ; De Groote, Jean ; De Meester, Karel ; De Nul, Eddy ; De Ranter, Jules ; Devreux, Pierre ; De Wit, Johan ; Gonella, Antonio ; Lakke, Allart ; Mannaers, Werner ; Mariën, Marcel ; Masaert, Jean-Georges ; Monteyne, Roland ; Merckaert, Patrick ; Minnaert, Frans ; Overbergh, Hilde
Van stof tot asse: 5 jaar Galerij De Ziener, Asse, 30 juni 1990 - 19 augustus 1990
boek